The complete mitochondrial genome of the copepod Calanus glacialis - Choquet, Marvin Raoul Charles Roger Ren; Alves Monteiro, Homére; Bengtsson-Palme, Johan; Hoarau, Galice Guillaume (Mitochondrial DNA Part B, 2017)
publishedVersion